The application of self‐limiting transgenic insects in managing resistance in experimental metapopulations - Zhou, L; Alphey, N; Walker, A; Traverse, L; Morrison, N; Bonsall, M; Raymond, B (Wiley, 2018)
1. The mass release of transgenic insects carrying female lethal self‐limiting genes can reduce pest insect populations. Substantial releases are also a novel resistance management tool, since wild type alleles conferring susceptibility to pesticides can dilute resistance alleles in target populations. However, a potential barrier is the need for large‐scale area wide releases. Here we address whether localized releases of transgenic insects could provide an alternative means of population suppression and resistance management, without serious loss of efficacy. 2. We used experimental mesocosms constituting insect metapopulations to explore the evolution of resistance to the Bacillus thuringiensis toxin Cry1Ac in a high‐dose/refugia landscape in the insect Plutella xylostella. We ran two selection experiments, the first compared the efficacy of ‘everywhere’ releases and negative controls to a spatially density‐dependent or ‘whack‐a‐mole’ strategy that concentrated release of transgenic insects in sub‐populations with elevated resistance. The second experiment tested the relative efficacy of whack‐a‐mole and everywhere releases under spatially homogenous and heterogeneous selection pressure. 3. The whack‐a‐mole releases were less effective than everywhere releases in terms of slowing the evolution of resistance, which, in the first experiment, largely prevented the evolution of resistance. In contrast to predictions, heterogeneous whack‐a‐mole releases were no more effective under heterogeneous selection pressure. Heterogeneous selection pressure did, however, reduce total insect population sizes. 4. Whack‐a‐mole releases provided early population suppression, indistinguishable from homogeneous everywhere releases. However, insect population densities tracked the evolution of resistance in this system, as phenotypic resistance provides access to additional diet containing the toxin Cry1Ac. Thus, as resistance levels diverged between treatments, carrying capacities and population sizes increased under the whack‐ a‐mole approach. 5. Synthesis and applications. Spatially density‐dependent releases of transgenic insects, particularly those targeting source populations at a landscape level, could suppress pest populations in the absence of area‐wide management. The benefits of self‐limiting transgenic insects were reduced in spatially localized releases, suggesting that they are not ideal for ‘spot’ treatment of resistance problems. Nevertheless, area‐wide and spatially heterogeneous releases could be used to support other resistance management interventions.